High-Fat Diet and Alcohol Intake Promotes Inflammation and Impairs Skin Wound Healing in Wistar Rats - Daiane Figueiredo Rosa; Mariáurea Matias Sarandy; Rômulo Dias Novaes; Mariella Bontempo Freitas; Maria do Carmo Gouveia Pelúzio; Reggiani Vilela Gonçalves (Hindawi Limited, 2018)
The wound-healing process is complex and remains a challenging process under the influence of several factors, including eating habits. As improper diets may lead to disorders such as dyslipidemia, insulin resistance, and chronic inflammation, potentially affecting the tissue ability to heal, we decided to investigate the effect of a high-fat diet and alcohol intake on the inflammatory process and skin wound healing in Wistar rats. Male rats (n=30) were individually housed in cages with food and water ad libitum (registration number 213/2014). After anesthesia, at day 40, three circular wounds (12 mm diameter) were made on the back of each animal, which were then randomly assorted into five treatment groups: C1 (control 1)-water via gavage and standard chow diet; C2 (control 2)-water (no gavage) and standard chow diet; AL (alcohol)-water (no gavage) and alcohol (40%) via gavage and standard chow diet; HF (high fat)-water (no gavage) and high-fat diet (50%); and HF + AL (alcohol/high fat)-water (no gavage), alcohol (40%) via gavage, and high-fat diet. Animals were treated for 61 days. Every seven days, the area and the rate of wound contraction were evaluated. Tissue samples were removed for histopathological analysis and biochemical analyses. Our results showed that wound contraction was not complete in the HF + AL rats. Two specific indices of wound-healing impairment (total cell number and levels of the inflammatory cytokine TGF-β) were increased in the HF + AL rats. We also observed decreased type I and III collagen fibers in the HF, AL, and HF + AL groups and increased oxidative stress markers in the same groups. We suggest that a high-fat diet combined with alcohol intake contributed to delayed skin wound healing through increase of the inflammatory phase and promoting oxidative stress, which may have led to morphological alterations and impaired matrix remodeling.